2010
DOI: 10.1093/imrn/rnn083
|View full text |Cite
|
Sign up to set email alerts
|

On Read's Type Operators on Hilbert Spaces

Abstract: Using Read's construction of operators without non-trivial invariant subspaces/subsets on ℓ1 or c0, we construct examples of operators on a Hilbert space whose set of hypercyclic vectors is "large" in various senses. We give an example of an operator such that the closure of every orbit is a closed subspace, and then, answering a question of D. Preiss, an example of an operator such that the set of its non-hypercyclic vectors is Gauss null. This operator has the property that it is orbit-unicellular, i.e. the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
56
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(59 citation statements)
references
References 16 publications
0
56
0
3
Order By: Relevance
“…In [40] it was shown that "many" Hilbert-space operators are orbit reflexive, for instance, normal, compact, algebraic operators and contractions. Examples of Hilbert-space operators that are not orbit-reflexive only recently appeared in [33,47]. It is an open question whether every power bounded operator T ∶ X → X is orbit reflexive.…”
Section: Corollary 92 Let T ∶ X → X Be An Operator If T Is Cyclic mentioning
confidence: 99%
“…In [40] it was shown that "many" Hilbert-space operators are orbit reflexive, for instance, normal, compact, algebraic operators and contractions. Examples of Hilbert-space operators that are not orbit-reflexive only recently appeared in [33,47]. It is an open question whether every power bounded operator T ∶ X → X is orbit reflexive.…”
Section: Corollary 92 Let T ∶ X → X Be An Operator If T Is Cyclic mentioning
confidence: 99%
“…In particular, in a profound study concerning spaces admitting operators without non-trivial invariant subspaces, Read has proved that every separable Banach space that contains either c 0 or a complemented subspace isomorphic to 1 or J ∞ , admits an operator without non-trivial closed invariant subspaces [30]. A comprehensive study of Read's methods of constructing operators with no non-trivial invariant subspaces can be found in [19,20]. Also recently a non-reflexive hereditarily indecomposable (HI) Banach space X K with the 'scalar plus compact' property has been constructed [7].…”
Section: Introductionmentioning
confidence: 99%
“…This was shown in the paper [12], where operators on the Hilbert space with few invariant closed subsets were constructed. We quote here the main result of [12] (combined with a remark from [13]), which shows which kind of properties of Read's type operators can be enforced in the Hilbertian setting. Theorem 1.3 [12].…”
Section: Introductionmentioning
confidence: 92%
“…We quote here the main result of [12] (combined with a remark from [13]), which shows which kind of properties of Read's type operators can be enforced in the Hilbertian setting. Theorem 1.3 [12]. There exists a bounded operator on a separable (real or complex) Hilbert space H which satisfies the following two properties:…”
Section: Introductionmentioning
confidence: 98%